Plasmacytoid dendritic cells: development, functions, and role in atherosclerotic inflammation - Chistiakov, Dimitry A.; Orekhov, Alexander N.; Sobenin, Igor A.; Bobryshev, Yuri V. (Frontiers in Physiology, 2014)
Plasmacytoid dendritic cells (pDCs) are a specialized subset of DCs that links innate and adaptive immunity. They sense viral and bacterial pathogens and release high levels of Type I interferons (IFN-I) in response to infection. pDCs were shown to contribute to inflammatory responses in the steady state and in pathology. In atherosclerosis, pDCs are involved in priming vascular inflammation and atherogenesis through production of IFN-I and chemokines that attract inflammatory cells to inflamed sites. pDCs also contribute to the proinflammatory activation of effector T cells, cytotoxic T cells, and conventional DCs. However, tolerogenic populations of pDCs are found that suppress atherosclerosis-associated inflammation through down-regulation of function and proliferation of proinflammatory T cell subsets and induction of regulatory T cells with potent immunomodulatory properties. Notably, atheroprotective tolerogenic DCs could be induced by certain self-antigens or bacterial antigens that suggests for great therapeutic potential of these DCs for development of DC-based anti-atherogenic vaccines.